Raw sewage science fiction bookworks 2010-2022 - Bell, Marc 1971- (Drawn and Quarterly, 2024)
"Canadian treasure Marc Bell returns with another gorgeous, confounding comic that redefines how an art book can tell a story and how a graphic novel can be an object first and story second. His internal monologue leaks out like static from a radio and informs the external; he's tying up loose ends; he's finishing long-paused sentences. Raw Sewage Science Fiction is about making art and understanding the results as autobiography. The process is a series of indignities, bubble wrapped frames, unpaid invoices, art lost through neglect or in the mail. Bell uses autofiction, collage, straight comix, tight cross hatching, loose doodling, repurposed in-flight magazines, envelopes, grocery lists, and snatches of late night CBC radio to examine a lost decade as he wanders from coast to coast. In a century, these will be our illuminated manuscripts, our sacred texts, our guides to life for now they are simply the truth--the irritating, confounding, glorious truth"--
Keywords: Bell, Marc / 1971- / Comic books, strips, etc; Cartoonists / Canada / Comic books, strips, etc; Graphic novels; Romans graphiques; Experimental comics; Autobiographical fiction; Comics (Graphic works); Bandes dessinées; Bildband